Cytotoxic Activity, Topoisomerase I Inhibition and In Silico Studies of New Sesquiterpene-aryl Ester Derivatives of (-) Drimenol - Ileana Araque; Javiera Ramírez; Rut Vergara; Jaime Mella; Pablo Aránguiz; Luis Espinoza; Waleska Vera; Iván Montenegro; Cristian O. Salas; Joan Villena; Mauricio A. Cuellar (Molecules, 2023)
In this study, we aimed to evaluate two sets of sesquiterpene-aryl derivatives linked by an ester bond, their cytotoxic activities, and their capacity to activate caspases 3/7 and inhibit human topoisomerase I (TOP1). A total of 13 compounds were synthesized from the natural sesquiterpene (-)-drimenol and their cytotoxic activity was evaluated in vitro against three cancer cell lines: PC-3 (prostate cancer), HT-29 (colon cancer), MCF-7 (breast cancer), and an immortalized non-tumoral cell line (MCF-10). From the results, it was observed that 6a was the most promising compound due to its cytotoxic effect on three cancer cell lines and its selectivity, 6a was 100-fold more selective than 5-FU in MCF-7 and 20-fold in PC-3. It was observed that 6a also induced apoptosis by caspases 3/7 activity using a Capsase-Glo-3/7 assay kit and inhibited TOP1. A possible binding mode of 6a in a complex with TOP1-DNA was proposed by docking and molecular dynamics studies. In addition, 6a was predicted to have a good pharmacokinetic profile for oral administration. Therefore, through this study, it was demonstrated that the drimane scaffold should be considered in the search of new antitumoral agents.